Hubungan di antara pergerakan mata dengan sistem akomodasi-vergens di kalangan pelajar Melayu di Universiti Kebangsaan Malaysia - Peron, Ceaser Jeffrey (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
The eye movement and the accommodation-vergence system play equally important roles in the reading process. However, the relationship between the eye movement and the accommodation-vergence system has not been investigated. Forty-five Malay Optometry students (30 emmetropes and 15 myopes) at the Universiti Kebangsaan Malaysia participated in this study. The eye movement was tested with the ‘Developmental Eye Movement’ (DEM) test. Amplitude of accommodation, accommodation accuracy, relative accommodation and accommodation facility were assessed under the accommodation system, while the near point of convergence, vergence facility and relative vergence were measured under the vergence system. The relationship between DEM and the vergence-accommodation system was analyzed based on the findings of the emmetropic subjects only. There was no significant correlation between DEM and the accommodation system (p>0.05). The correlation between DEM and vergence system was found significant for vertical phoria at 6m only (p<0.05). The effect of refractive error on the DEM was further investigated by comparing the myopes and emmetropes. Refraction was found to have no significant effect on the DEM (p>0.05). The eye movement is not correlated with the accommodation system, but is correlated with the vertical phoria at far of the vergence system. The DEM is not affected by the types of refraction.